Gender Role Models in Education - Sofoklis Goulas; Bhagya N. Gunawardena; Rigissa Megalokonomou; Yves Zenou (CESifo GmbH, 2024)
Using Greek administrative data, we examine the impact of being randomly assigned to a classroom with a same-gender top-performing student on both short- and long-term educational outcomes. These top performers are tasked with keeping classroom attendance records, which positions them as role models. Both male and female students are influenced by the performance of a same-gender top performer and experience both spillover and conformist effects. However, only female students show significant positive effects from the presence of a same-gender role model. Specifically, female students improved their science test scores by 4 percent of a standard deviation, were 2.5 percentage points more likely to choose a STEM track, and were more likely to apply for and enroll in a STEM university degree 3 years later. These effects were most pronounced in lower-income neighborhoods. Our findings suggest that same-gender peer role models could reduce the underrepresentation of qualified females in STEM fields by approximately 3 percent. We further validate our findings through a lab-in-the-field experiment, in which students rated the perceived influence of randomized hypothetical top-performer profiles. The results suggest that the influence of same-gender top performers is primarily driven by exposure-related factors (increased perception of distinction feasibility and self-confidence) rather than direct interactions.
Keywords: J24; J16; I24; I26; 330; gender gap; lab-in-the-field experiment; natural experiment; random peer group formation; role models; self-confidence; STEM